Characterization of Atmospheric Absorption in the 60 GHz Frequency Band Using a Multi-Pole Material Model - (:unkn) unknown (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2019)
Atmospheric attenuation of electromagnetic signals at the 60 GHz frequency band is dominated by oxygen absorption which represents a major obstacle to 5G communications using this band. So far, only empirical equations that fit the experimental absorption data have been reported. These empirical models are not suitable to employ in standard full-wave electromagnetic simulators based on the numerical solution of Maxwell's equations. In this paper, a frequency-dependent material model for atmospheric absorption at the 60 GHz band is presented. Further, a numerical simulator that incorporates this multi-pole material dispersion model and uses the rotating boundary conditions to allow for long propagation distances is developed. The simulation algorithm is based on the auxiliary differential equation finite-difference time-domain (ADE-FDTD) technique which implements the general electric polarization formulation. The results are useful in the prediction of propagation power loss between line-of-sight communication links and in the planning and positioning of ground and air-borne facilities.
Keywords: 5G communications; 60GHz frequency band; atmospheric attenuation; FDTD method; lorentz model; oxygen absorption; PROPAGATION